A Clinico-Pharmacological Aspect of Kwatha Kalpana in ENT Disorders (AYUSHDHARA, 2021)
Ayurveda is split into many branches. The branch which deal with the drug and use within the style of medicine for the treatment of diseases is thought as Bhaishajya Kalpana (Ayurvedic Pharmaceutics). Bhaishajya Kalpana endorses the five fundamental dosage form, namely Swaras (juice), Kalka (paste), Kwatha (decoction), Hima (cold infusion), Phant (hot infusion). This is often the real source of success for physicians. Among them, Kwatha Kalpana (decoction types of medicine) is that the most vital and widely used dosage form in Ayurvedic pharmaceutic. Shalakyatantra (treatment of disorder above clavicle) is one in all Ashtanga Ayurveda (eight clinical branches of Ayurveda), coping with the study of diseases occurring above the Jatru (part of body above the clavicle), which has Shiras (head), Karna (ear), Nasa (nose), Netra (eyes) and Mukha (mouth) and their management. Shalakyatantra is primarily concerned with preserving and restoring the health of the Indriyas (senses). In modern science ear, nose and throat are studied collectively within the specialized field called otolaryngology or upper tract diseases which is colloquially referred to as ENT. The monotonous mechanical life style, faulty food habits, restless schedule, stress, overpopulation, overcrowding of vehicle leading to the sound and air pollution, junk food habits is causing hazardous effects of receptor. Ayurvedic system of drug enunciates more of preventive measures which are lacking in contemporary science. Identifying the Nidana (etiology) and avoiding it forms the key role in preventing most of the ENT disorders. Hence, it’s is highly essential to spot and treat the common ENT disorder seen in clinical practice with Ayurvedic measures specially Kwath Kalpana. In present article a clinic-pharmacological aspect of the Kwath Kaplana is discussed with reference to ENT diseases.